Peer‐to‐peer sharing platforms with quality differentiation: Manufacturer's strategic decision under sharing economy. Issue 2 (17th October 2022) - Guan, Huiqi; Geng, Xin; Gurnani, Haresh
Abstract: As peer‐to‐peer sharing platforms emerge in the downstream market, upstream product manufacturers may build their exclusive sharing platform, seeking benefits from the sharing market. To study the profit and welfare implications of the emergence of sharing economy and manufacturer's platform‐building strategy, we employ a vertically differentiated duopoly setting and consider three scenarios: no‐sharing benchmark, a single third‐party platform emerged, and manufacturer‐built platform co‐existing with the third‐party platform. Formulating and solving the game in each scenario, we compare the equilibrium outcomes, including manufacturers' profits, consumer surplus and social welfare, before and after scenario transitions. For the manufacturers' profits, no matter which manufacturer builds the platform in presence of the third‐party platform, that manufacturer will be better off, whereas the opponent manufacturer may also benefit, depending on the quality differentiation perceived by consumers in the product selling market and in the sharing market. Moreover, when comparing against the no‐sharing benchmark, the manufacturers benefit from the sharing only when the quality differentiation is large enough and the production cost is not small. For the welfare implication, if the renters derive the same usage utility as the owners in the sharing market, the consumer surplus and the social welfare will always increase as the third‐party platform emerges or a manufacturer builds its platform. Otherwise, either platform could hurt the consumer surplus and the social welfare, especially when the quality differentiation is large. Our research highlights the innovative platform‐building strategy in the presence of peer‐to‐peer sharing economy and offers important insights to all market participants.